Internet and Pediatric Dermatology. What's new in the net? A little guide, step by step, to the potential of Internet for the Pediatrician and Dermatologist. - Cutrone, M. (European Journal of Pediatric Dermatology, 2018)
The Author proposes to the reader the use of Internet to enter, by sailing in the telematic space, the whole planet of information, that are now completely available for him/her, thanks to a computer, a modem and a simple phone. After a short introduction to the use of Internet, a list of sites follows, with the relevant addresses, to be visited, initially to play and satisfy one's curiosity, later on to personally verify the real usefulness of this new type of integrated system of digital communication.